2023
DOI: 10.1097/md.0000000000032797
|View full text |Cite
|
Sign up to set email alerts
|

Using temporal heatmaps to identify worthwhile articles on immune checkpoint blockade for melanoma (ICBM) in Mainland China, Hong Kong, and Taiwan since 2000: A bibliometric analysis

Abstract: Background: Melanoma is a life-threatening form of skin cancer. Due to its remarkable effectiveness, the immune checkpoint blockade is widely used to treat melanoma (ICBM). No research has been conducted on ICBM for identifying the most readable articles. A bibliometric analysis of 100 top-cited ICBM (T100ICBM) in recent decades is required to highlight articles worth reading. Methods: Based on the Web of Science Core Collection, we summarized the articles on ICBM published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…The descriptive, diagnostic, predictive, and prescriptive analytics (DDPP) model was employed in a structured bibliometric analysis, as referenced in studies. [20][21][22][23] This model enables us to comprehend the development of various entities, such as authors, affiliated countries, keywords, research topics (e.g., research themes), or journals. It also allows us to discern patterns in scientific studies across different subject fields, as indicated in.…”
Section: Tmsd Merged To a Ddpp Model In Bibliometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive, diagnostic, predictive, and prescriptive analytics (DDPP) model was employed in a structured bibliometric analysis, as referenced in studies. [20][21][22][23] This model enables us to comprehend the development of various entities, such as authors, affiliated countries, keywords, research topics (e.g., research themes), or journals. It also allows us to discern patterns in scientific studies across different subject fields, as indicated in.…”
Section: Tmsd Merged To a Ddpp Model In Bibliometricsmentioning
confidence: 99%
“…Another important aspect of this research is its use of the DDPP model. [20][21][22] This model is a versatile tool that can be used for descriptive, diagnostic, predictive, and prescriptive analytics. The choice of analytic approach depends on the nature of the question and the insights that are being sought.…”
Section: Implications and Possible Changesmentioning
confidence: 99%
“…The TBG has been illustrated in bibliographical studies, [2,27,35] but no such IP points combined on the TBG, as we demonstrated in Figure 6. As such, the temporal visualization can be further improved when compared to the previous studies [30,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] using trend analysis.…”
Section: Contributions Of the Studymentioning
confidence: 99%
“…Furthermore, citation prediction [34][35][36][37] has been employed in bibliometrics to predict article citations based on weighted scores of article keywords, and THM has been applied to display articles worth reading. [31,32,38] In this manner, the DDPP model can be used to conduct a comprehensive bibliometric analysis of MA articles.…”
Section: Citation Prediction and Article Worth Reading Required In Bi...mentioning
confidence: 99%
“…Using THM, [31,32,38] we extracted articles worth reading from T100 articles, which were determined based on their high citations and increasing growth rates over the past 4 years (from 2019 to 2022).…”
Section: Prescriptive Analytics In T100 Articlesmentioning
confidence: 99%